2020
DOI: 10.31234/osf.io/pwkzm
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Indirect illusory inferences from disjunction: a new bridge between deductive inference and representativeness

Abstract: We provide a new link between deductive and probabilistic reasoning fallacies. Illusory inferences from disjunction are a broad class of deductive fallacies traditionally explained by recourse to a matching procedure that looks for content overlap between premises. In two behavioral experiments, we show that this phenomenon is instead sensitive to real-world causal dependencies and not to exact content overlap. A group of participants rated the strength of the causal dependence between pairs of sentences. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…The model theory predicts and explains such cognitive illusions: they occur whenever, for instance, a reasoner infers that an impossible conclusion is possible, or vice versa. Research has revealed illusory inferences across a wide variety of reasoning domains, such as with reasoning about probabilities and conditionals (Johnson‐Laird & Savary, 1996), disjunctions (Khemlani & Johnson‐Laird, 2009; Sablé‐Meyer & Mascarenhas, 2021), and Boolean concepts (Goodwin & Johnson‐Laird, 2010). The theory accordingly predicts that illusions should occur in bouletic reasoning.…”
Section: The Mental Representation Of Desirementioning
confidence: 99%
“…The model theory predicts and explains such cognitive illusions: they occur whenever, for instance, a reasoner infers that an impossible conclusion is possible, or vice versa. Research has revealed illusory inferences across a wide variety of reasoning domains, such as with reasoning about probabilities and conditionals (Johnson‐Laird & Savary, 1996), disjunctions (Khemlani & Johnson‐Laird, 2009; Sablé‐Meyer & Mascarenhas, 2021), and Boolean concepts (Goodwin & Johnson‐Laird, 2010). The theory accordingly predicts that illusions should occur in bouletic reasoning.…”
Section: The Mental Representation Of Desirementioning
confidence: 99%